If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -1y = -18 + 7y Solving 14 + -1y = -18 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 14 + -1y + -7y = -18 + 7y + -7y Combine like terms: -1y + -7y = -8y 14 + -8y = -18 + 7y + -7y Combine like terms: 7y + -7y = 0 14 + -8y = -18 + 0 14 + -8y = -18 Add '-14' to each side of the equation. 14 + -14 + -8y = -18 + -14 Combine like terms: 14 + -14 = 0 0 + -8y = -18 + -14 -8y = -18 + -14 Combine like terms: -18 + -14 = -32 -8y = -32 Divide each side by '-8'. y = 4 Simplifying y = 4
| z=y+12 | | -8t=16 | | 12x+9=7x+29 | | 7=14+x | | -2y=x+7 | | 8x-15=81 | | d=3h | | (x+3)2-7(x+3)+10=0 | | 6x^9y^7+18x^7y^6+42xy=0 | | 2b-8=b+7 | | 9x^9y^7+18x^7y^6+42xy=0 | | 7x+2+6x+7=12x+5 | | 2x=5+5y | | 3.5x-0.5=3 | | 4x^3+6x^2-12x-2=0 | | 3(7x)=105 | | 45x^2-6x-24=0 | | x-12=-8+2x | | (Y^2-7y)(y-5)= | | 6x+5=85-4x | | 6-5(3x-2)=-44 | | n=0.04x-78.50 | | 5-4(x+3)=5 | | 3-y=2x | | (y^2-7x)(y-5)= | | 2y-6y-10=-2 | | 3x=-2y+10 | | r^2+8r+7=0 | | 3x+2x+7=41 | | 3x^2+7x-6=0 | | 2d-10=6(7-4d) | | 7x+2y=-8 |